Pengaruh Kecanggihan Teknologi Informasi dan Penggunaan Sistem Informasi Akuntansi Terhadap Kemampuan Kinerja Individu: Studi Kasus pada PT Tri Pranata Jaya - Fatwa Wisnu Pranoto; Suluh Agus Hendrawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of advanced information technology and the use of accounting information systems on individual performance capabilities at PT Tri Pranata Jaya. The research employs a descriptive method with a quantitative approach. Data were collected through purposive sampling involving 45 respondents from the administrative department. The results indicate that advanced information technology has a positive and significant effect on individual performance capabilities. Furthermore, the use of accounting information systems also positively and significantly influences individual performance capabilities. Simultaneously, advanced information technology and the use of accounting information systems have been proven to enhance individual performance capabilities.